1965
DOI: 10.1577/1548-8659(1965)94[311:aaotvo]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Variability of Fish Populations Taken by Otter Trawl in Biscayne Bay, Florida

Abstract: Three bottom habitats in Biscayne Bay were sampled by 120 trawl samples taken during both day and night from April to August 1963. Daylight samples contained 1,391 fishes representing 41 species. Night samples contained 1,440 fishes and 49 species. The number of species per sample followed a Poisson distribution, the number of individuals per sample followed a negative binomial distribution, and the number of individuals per species followed Fisherˈs logarithmic series. The following generalizations apply to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The highest value in one sample was 0.47 g dry/m a found in June 1973. Roessler (1965). The wet weight of fish per unit area varies from a daytime high of 15 g/m a in September 1972, to a nighttime low of 0.6 g/m a in March 1973 (Table 3) However, the analysis of gut contents is qualitative and the percentages in Table 4 refer to the relative number of fish of each species examined which were empty or which contained identifiable remains from each prey taxon.…”
Section: Resultsmentioning
confidence: 99%
“…The highest value in one sample was 0.47 g dry/m a found in June 1973. Roessler (1965). The wet weight of fish per unit area varies from a daytime high of 15 g/m a in September 1972, to a nighttime low of 0.6 g/m a in March 1973 (Table 3) However, the analysis of gut contents is qualitative and the percentages in Table 4 refer to the relative number of fish of each species examined which were empty or which contained identifiable remains from each prey taxon.…”
Section: Resultsmentioning
confidence: 99%
“…Fish densities are typically greater in grass bed habitat within South Florida's estuaries and coastal lagoons than in adjacent habitats (Reid 1954, Tabb et al 1962, Roessler 1965, Yokel 1975, Weinstein et al 1977. Grass beds provide cover and protection from predation for animals living in them (Zieman 1982, Heck et al 1997.…”
Section: Relationship Of Submerged Aquatic Vegetation and Salinity Tomentioning
confidence: 99%
“…In an early study of Biscayne Bay, Roessler (1965) found that samples collected at night had significantly greater numbers* of fishes than had those collected in •A referee points out that species identity can be most important.-Ed. daytime; however, in the studies made at Turkey Point, comparisons of day and night catches showed no significant differences (Roessler & Tabb, 1974).…”
Section: Biscayne Baymentioning
confidence: 99%